Different Doses of Intravenous Tissue-Type Plasminogen Activator for Acute Ischemic Stroke: A Network Meta-Analysis - Li, Bing-Hu; Wang, Jian-Hong; Wang, Han; Wang, Duo-Zi; Yang, Shu; Guo, Fu-Qiang; Yu, Neng-Wei (Frontiers in Neurology, 2022)
Background This study aims to assess the efficacy and safety of different doses of intravenous tissue-type plasminogen activator (tPA) for acute ischemic stroke (AIS) by adopting a network meta-analysis (NMA). Methods Studies comparing different doses of tPA in AIS were identified by retrieving electronic databases. NMAs of outcome measures included favorable functional outcome with a modified Rankin scale score (mRS) of 0 or 1 at 3 months after treatment (3M-FF), the functional independence with a mRS of 0, 1, or 2 at 3 months (3M-FI), symptomatic intracranial hemorrhage (sICH) and 3-month all-cause mortality (3M-M). Symptomatic intracranial hemorrhage (sICH) and 3-month all-cause mortality (3M-M) were assessed. Probability-based ranking and surface under cumulative ranking (SUCRA) were performed to identify the best dose of tPA. Inconsistency was evaluated by node-splitting analysis and a loop-specific approach. Publication bias was analyzed by funnel plots. Results A total of 14 studies were included in the quantitative synthesis. The NMA results revealed no difference among low (<0.7 mg/kg), moderate (0.8 mg/kg), and standard (0.9 mg/kg) doses of tPA with regard to efficacy and safety. The SUCRAs of 3M-FF and 3M-FI showed that the standard dose ranked first, the moderate dose ranked second, and the low dose ranked third. The SUCRA of sICH showed that the standard dose ranked first (78.1%), the low dose ranked second (61.0%), and the moderate dose ranked third (11.0%). The SUCRAs of 3-month mortality showed that the standard dose ranked first (73.2%), the moderate dose ranked second (40.8%), and the low dose ranked third (36.1%). No significant inconsistency was shown by node-splitting analysis and no publication bias was shown in funnel plots. Conclusion Lower dose tPA was comparable to the standard dose with regard to efficacy and safety. Based on the SUCRA results and American Heart Association/American Stroke Association (AHA/ASA) guidelines, the standard dose was still the optimal selection for AIS.